Stylish but Broke: The Relationship between Social Media Self-Presentation, Lifestyle, and Financial Planning as a Mediator of Young People's Financial Awareness - Gigih Hilmiawan; Irhas Badruzaman; Zulfatun Ruscitasari; Anik Puji Handayani; Idzhar Hanan Nurrohim (CV Edujavare Publishing, 2026)
Social media (Instagram, TikTok, Snapchat) encourages young people, including those in Indonesia, to project an image of their lifestyle and social status online, but this frequently leads to the'stylish but broke' phenomenon, in which a polished visual image contrasts with their actual financial circumstances due to conspicuous consumption, materialism, and social pressure. The purpose of this study is to investigate the link between social media use and lifestyle on young people's financial awareness, with financial planning serving as a mediating variable to explain how digital exposure might translate into an understanding of appropriate financial management practices. A sample of 100 respondents was found acceptable for PLS-SEM analysis. Primary data were acquired using an online survey with a standardised questionnaire. The study's participants were young people who use social media regularly. Purposive sampling was used. The study's findings show that social media use and lifestyle have a favourable impact on financial planning, while financial planning has a positive and substantial impact on the younger generation's financial awareness. Furthermore, financial planning has been proven to operate as a full mediator, bridging the relationship between social media use and lifestyle on financial awareness. These data imply that the influence of social media and lifestyle on financial behaviour is indirect, rather occurring through individuals' capacity to arrange their finances.